Editorial Volume 18 Issue 5: Special Issue on Sustainable Transformation Towards Digitalization - Senny Luckyardi (Australasian Accounting, Business and Finance Journal, 2024)
This Special Issue of the Australasian Accounting Business and Finance Journal (AABFJ) arises from the Sustainable Transformation towards Digitalization of the 7th International Conference on Business, Economics, Social Sciences, and Humanities (ICOBEST 2024). This conference is hosted by Universitas Komputer Indonesia, Bandung, Indonesia. The conference revolves around the theme of Sustainable Transformation towards Digitalization based on Environmental, Social, and Governance (ESG) principles. ESG refers to a set of guidelines used to evaluate and manage businesses' performance concerning the environment, society, and corporate governance. It serves as a means of assessing companies' responsibility towards economic advancement, environmental preservation, and social welfare. Therefore, this special issue sheds light on utilizing digitalization as a tool for advancing sustainability and responsible business practices, aligning with research by Inta Budi Setya Nusa et al., (2024), which suggests the utilization of AI and big data technologies in accounting. This research offers valuable insights into the profession of accounting educators, enabling teachers to develop better curricula and equip students with the necessary skills to thrive in an increasingly digitally interconnected workplace.
Keywords: Editorial; Special Issue; Special Issue on Sustainable Transformation Towards Digitalization